2014
DOI: 10.3389/fpsyg.2014.01366
|View full text |Cite
|
Sign up to set email alerts
|

Can the computer replace the adult for storybook reading? A meta-analysis on the effects of multimedia stories as compared to sharing print stories with an adult

Abstract: The present meta-analysis challenges the notion that young children necessarily need adult scaffolding in order to understand a narrative story and learn words as long as they encounter optimally designed multimedia stories. Including 29 studies and 1272 children, multimedia stories were found more beneficial than encounters with traditional story materials that did not include the help of an adult for story comprehension (g+ = 0.40, k = 18) as well as vocabulary (g+ = 0.30, k = 11). However, no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 57 publications
(82 reference statements)
7
48
2
4
Order By: Relevance
“…These results were remarkably different from Takacs, Swart, and Bus' who reported that multimedia components promoted children's story learning [76]. Like previous studies, this meta-analysis noted that games distracted from children's learning, but also found that, in the absence of an adult, interactive storybooks were more useful than children reading on their own [76].…”
Section: Technology and Educationcontrasting
confidence: 55%
See 1 more Smart Citation
“…These results were remarkably different from Takacs, Swart, and Bus' who reported that multimedia components promoted children's story learning [76]. Like previous studies, this meta-analysis noted that games distracted from children's learning, but also found that, in the absence of an adult, interactive storybooks were more useful than children reading on their own [76].…”
Section: Technology and Educationcontrasting
confidence: 55%
“…Like previous studies, this meta-analysis noted that games distracted from children's learning, but also found that, in the absence of an adult, interactive storybooks were more useful than children reading on their own [76]. Takacs et al concluded that the scaffolding provided by multimedia storybooks was similar to that provided by adults reading a narrative [76].…”
Section: Technology and Educationmentioning
confidence: 70%
“…Previous studies have shown varying results for the cognitive factors of children’s story recall and comprehension when reading from paper or screen: for example, De Jong and Bus (2002) found better learning of content for pre-schoolers being read to by an adult from a paper book than from an e-book, but Takacs et al (2014) noted that e-books can support word learning and story comprehension just as well as print stories when they use well-designed multi-media extras. Our study used digital texts with no multimedia extras, in order to compare paper to screens more directly in relation to recall, and yielded no difference by reading medium.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis by Takacs et al . (), with 29 studies and 1,272 children, found that multimedia features (in electronic storybooks) are more effective than print books when read without adult support (in relation to children's story comprehension and vocabulary). A later meta‐analysis by the same research team (Takacs et al ., ), with 43 studies and 2,147 children, found that unlike multimedia features, interactivity did not support children's story comprehension and vocabulary learning.…”
Section: Key Theoretical Empirical and Design Issues In The Fieldmentioning
confidence: 99%